Estudio de métodos y tiempos en el proceso productivo de la línea de camisas del taller de confecciones la casa uniforme del caribe para mejorar y/o fortalecer la productividad y los sistemas de trabajo en la empresa (2020)
t the time we live, Siglo XXI, (industrial) companies march through conditions that a demanding and active market imposes, in which efficiency and performance from all perspectives of the production process allow the organization to succeed in the market . The companies dedicated to making the uniforms of Institutions such as SENA, in the city of Cartagena, need to carry out productive studies in order to meet the demand and demands of this market. To address this problem or concern, the study of methods and work times is proposed, which seeks to produce more units of products in less time, improve efficiency at work stations, diagnose the current process of product development: in this case the SENA uniform shirts, and identify those activities or stages of the process that prevent a greater volume of production. This work presents the results of an investigation carried out in the Clothing Production Center of the company LA CASA DEL UNIFORME DEL CARIBE. Within business decisions, it is necessary to focus on all types of production within business growth and development, improving productivity and protecting the integrity (health and safety at work) of those who make up this organization. For this reason, an internal change is approved by the directors of the company LA CASA DEL UNIFORME DEL CARIBE, a company established in the city of Cartagena, to which we developed this proposal to improve its operations, based on the study of times of production, to optimize the processes and the economy of the company. Under this study, which is being carried out, various problems have been identified in the production area, such as the fact of having two separate places for cutting and making its flagship product: shirts, which prevents having ordered spaces in the operation and this in itself generates high manufacturing times, waste of raw material and disorders of the physical plant. This document presents the analysis of the study of methods and times in accordance with the processes carried out for the making of shirts, to fully and excellently satisfy the manufacture of the product and at the same time the degree option (Applied project) before the faculty of Industrial Engineering from the ANTONIO NARÑO UNIVERSITY HEADQUARTERS CARTAGENA / UAN. We suggest and propose a proposal to improve working conditions, use of materials, equipment, and labor, since industrial engineering tends to “Study methods and times as a tool used to calculate the times required by a qualified operator. to perform a certain task following a pre-established method; its objective is to analyze the productivity of a process in order to know its efficiency and effectiveness, and thus develop production improvement methods ”(summary of industrial organization